Marine biodiversity awareness and engagement among students: Implications for local conservation policy - Zydrick L. Avelino (University of Muhammadiyah Malang, 2026)
Background: As a municipality hosting a rich coastal ecosystem, Bagac serves as a vital focal point for translating global marine conservation frameworks into local action. Objectives: This study aimed to evaluate higher education students' awareness of marine biodiversity alongside Sustainable Development Goal (SDG) 14—to conserve and sustainably use the oceans, seas, and marine resources—and explore the translational gap between academic research and policy engagement. Methods: Utilizing a descriptive cross-sectional survey design, data were collected from 383 undergraduate students using a validated instrument that concurrently captured quantitative ratings and qualitative open-ended responses. Results: Quantitative results revealed a significant skill-gap paradox: while students exhibited strong pro-conservation values, 86.9% had never participated in marine research. A strong correlation existed between perceived institutional engagement and academic policy awareness (ρ = 0.795, p < .001), alongside a significant curricular divide in baseline awareness across academic disciplines (p = .003). Qualitative thematic analysis attributed this translational gap to structural barriers, specifically jargon-heavy academic language and the challenges in collaborative platforms with local government. Conclusion: Theoretical environmental awareness experiences challenges in policy translation without active institutional scaffolding. Universities may bridge this science-to-policy gap by systematically integrating SDG 14 across all curricula and establishing platforms to train students in translating research into actionable local policy.